Gender differences in response to differing antidepressant drug classes: two negative studies - PARKER, G.; PARKER, K.; AUSTIN, M.-P.; MITCHELL, P.; BROTCHIE, H. (Psychological medicine, 2003)
Background. A recent US study presented data suggesting that depressed women are more likely to respond to selective serotonin reuptake inhibitor (SSRI) than tricyclic (TCA) antidepressant drug therapies. We have undertaken replication studies in two independent databases. Method. We have examined for gender differences in SSRI and TCA antidepressant response in both retrospective and prospective naturalistic uncontrolled studies, and in subsets of melancholic and non-melancholic depressed subjects. As the US study had indicated that women under the age of 40 years were particularly likely to show a differential response to SSRIs, we examined for age, gender and interactional effects. In addition, we examined for differential SSRI and TCA responsiveness in a subset of patients who had received drugs from both classes. Results. We failed to find evidence of women having a preferential response to SSRI medication or, conversely, of men having a superior response to TCA medication. Older age, however, was associated with a superior TCA response and younger age with a superior SSRI response. Conclusion. As few studies have examined for differential gender and age effects in response to narrow action and broad action antidepressant drugs across major depressive subtypes, gender differential effects remain to be established.